2021
DOI: 10.1155/2021/8847158
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Fracture Patterns and Crack Propagation of Sandstone Based on Acoustic Emission

Abstract: To investigate the fracture pattern and crack propagation of rock under different stresses, Brazilian split tests, preset angle tests, and uniaxial compression acoustic emission (AE) tests were carried out on sandstone to obtain the mechanical parameters and AE signals of the whole test process. Based on the analysis of the distribution of the characteristic AE indicators rise time/amplitude (RA) and average frequency (AF) combined with the core definition of areal density, the test results showed the followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 35 publications
1
13
1
Order By: Relevance
“…The sudden increase of counts in the third period indicated that AE was extremely active and the development of cracks was extremely rapid. The rupture precursor recognition characteristics were that the counts keep fluctuating within a medium to high level with an obvious aggregation, but suddenly become gentle when the stress was the highest [27]. In the areas of rupture precursor characteristics in Fig.…”
Section: Acoustic Emission Activitymentioning
confidence: 89%
See 1 more Smart Citation
“…The sudden increase of counts in the third period indicated that AE was extremely active and the development of cracks was extremely rapid. The rupture precursor recognition characteristics were that the counts keep fluctuating within a medium to high level with an obvious aggregation, but suddenly become gentle when the stress was the highest [27]. In the areas of rupture precursor characteristics in Fig.…”
Section: Acoustic Emission Activitymentioning
confidence: 89%
“…5 reveals the relationship between AE energy, cumulative energy, and stress vs. time. The results showed that the energy and accumulated energy could be divided into three stages with the loading process: gentle period, steady period and steep period [27]. Each period could correspond to the three loading stages in Section 3.1.…”
Section: Acoustic Emission Activitymentioning
confidence: 99%
“…Different types of cracks correspond to different AE waveforms. Tensile cracks are generally considered to have low RA values (rise time/amplitude) and high AF values (ring count/duration), while shear cracks have high RA values and low AF values, and tension-shear cracks have low RA values and low AF values [ 43 , 44 ]. The failure mode of the AE signal in concrete can be analyzed according to Figure 10 .…”
Section: Discussionmentioning
confidence: 99%
“…When RA, that is, the ratio of rise-time to the peak amplitude, is greater than the AF, that is, the average frequency given by the ratio of hit count by event duration, the AE event source is originated by a shear crack, and for the converse, it is a tensile crack [23,40]. Researchers have used the AF-RA crack classification concept for characterizing the AE source mechanism under different loading conditions on different types of rocks, such as sandstone, granite, diorite, and marble, as well as plain and reinforced concrete [5,23,27,30,40,41,42,49].…”
Section: Figmentioning
confidence: 99%